Family Support on the Provision of Vitamin A to TOddlers - Kiki Riskianti Nanda (Journal of Public Health and Pharmacy, 2023)
Vitamin A is an element of Vitamin that is very important for the development of Toddlers, but is sometimes neglected by mothers so that it requires support from the closest people, such as family and health workers. This research method is quantitative with a cross sectional study approach. This research was carried out in Makassar in 2021, the sample taken was 140 people. Analysis of the data used using the chi square test with = 0.05 provided that if the value of p <0.05 then there is a significant relationship between the dependent and independent variables. The data were analyzed using SPSS Version 24. The results of this study with a significance value of 0.05, it means that there is a relationship between family support and the administration of vitamin A. Conclusion: The role of cadres and families is needed to support the administration of vitamin A to toddlers to prevent unwanted risks.